PENDUGAAN UKURAN PERTAMA KALI MATANG GONAD IKAN SENGGARINGAN (Mystus negriceps) DI SUNGAI KLAWING, PURBALINGGA JAWA TENGAH - Benny Heltonika; ridwan affandi; iman supriatna (Jurnal Akuakultur Rawa Indonesia, 2016)
ABSTRACT Fish reproduction aspect must be know to improve some fish to be broodstock, like as food needed, water quality etc.Â  The other aspect must be know is how long body size at the first time maturity.Â  Size body at the first time maturity in fish is important information, because this information will give us how long in body some fish begin done reproduction. This research was conducted in Klaving river, Purbalingga residence of Midle Java, fishes were sampled twice a month (March to December). The variable measured were total length where fish reach gonad maturity on 4th level. The result of this research was shown that 148.9010 mm of body size for Mystus negriceps reach the first time maturity. Keywords : reproduction, first time maturity, Klawing river